Survey of ICT and Education in Africa : South Africa Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. In all the different facets of the ICTs for education prism, South Africa boasts more than a decade of accumulated experience from its wide range of projects and programs pioneered by noteworthy champions across the stakeholder spectrum of communities, the private sector, civil society, donor, development, and government agencies. A variety of tested models on ICT access, digital content development, teacher training and professional development, optimal usage, partnerships, and resource mobilization have encouraged significant learning among innovators, practitioners, and policymakers. The scale of all these interventions to date has led to at least 22 percent computer penetration in all public schools. While South Africa has a policy on e-education only for the schools and Further Education and Training (FET) college sectors, herein too lay animated debate on the optimal ways to implement the policy. Over the coming period, with South Africa acting as host for the 2010 World Cup and the national government embarking on accelerated economic growth strategies, the race is on to move to broadband and promote ubiquitous ICT access. South African education institutions in general, and the schools and FET college sectors in particular, are set to grow significantly in ICT access, teacher training, and professional development and usage. However, major challenges still need to be overcome, such as the lack of a comprehensive policy on ICTs in education that covers all sectors in education, the continued need for leadership and co-ordination of various initiatives, the promotion of enhanced learning through optimal usage of the technologies, and, above all, the need to demonstrate the value of the investment in ICTs through improved performance of learners and teachers and improved employability in the changing labor market.